2022
DOI: 10.1590/fst.08521
|View full text |Cite
|
Sign up to set email alerts
|

The real role of select herb and spice extracts against Bacillus cereus ATCC 14579 growth in cooked rice

Abstract: This study aimed to investigate the effect of select spices and herbs added to cooked rice in the growth of Bacillus cereus. The results showed the actual role of herbs and spices as food flavoring ingredients rather than acting as a preservative agent. Herbs and spices extracts were added to rice before and after the cooking process, then observed the differences in Bacillus cereus growth. From all herb and spices extract used, clove was the most effective one against B. cereus. It provided a good zone of inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…Similar report of ginger, having low activity against S. pneumonia was made by Horne et al (2001). The antimicrobial activity of ginger extract, concentrates and essential oil, as reported, showed promising inhibitory effect against some pathogens such as Bacillus cereus, Staphylococcus aureus, Pseudomonas aeruginosa (Albaridi and Yehia, 2021;Sanusi et al, 2019;Riaz et al, 2015;Harmalkar and Desai, 2011), Escherichia coli, Candida albicans and Aspergillus niger (Kumar et al, 2016). Such effect can be attributed to its constituent monoterpenes and sesquiterpenes, as they are capable of altering the permeability and fluidity of the plasma membrane of microorganisms (Lopez et al, 2017).…”
Section: Resultssupporting
confidence: 60%
“…Similar report of ginger, having low activity against S. pneumonia was made by Horne et al (2001). The antimicrobial activity of ginger extract, concentrates and essential oil, as reported, showed promising inhibitory effect against some pathogens such as Bacillus cereus, Staphylococcus aureus, Pseudomonas aeruginosa (Albaridi and Yehia, 2021;Sanusi et al, 2019;Riaz et al, 2015;Harmalkar and Desai, 2011), Escherichia coli, Candida albicans and Aspergillus niger (Kumar et al, 2016). Such effect can be attributed to its constituent monoterpenes and sesquiterpenes, as they are capable of altering the permeability and fluidity of the plasma membrane of microorganisms (Lopez et al, 2017).…”
Section: Resultssupporting
confidence: 60%
“…At the same time, Bacillus and Micrococcus were prevalent pathogens associated with grain contamination, particularly rice [1]. The bacterial strain of B. cereus develops rapidly and generates toxins on boiled rice and other carbohydrate-rich meals kept at room temperature [11]. There is a growing global need for high-quality, safe food free of chemical, physical, and microbial contamination.…”
Section: Introductionmentioning
confidence: 99%
“…Use of spice and plant extracts has generally gained wide acceptability [11][12][13][14] because they are easy to use and highly efficient. Spices have beneficial biological functions such as bactericidal, bacteriostatic, fungistatic, anthelmintic, medicinal and flavouring properties.…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20][21] Ginger extracts were reported to have exerted an inhibitory effect against Bacillus cereus, S. aureus and P. aeruginosa. [14][15][16][17][18][19][20][21] In a study conducted using different spices (cinnamon, black pepper, cloves, turmeric and ajwain), antimicrobial zones of inhibition against S. aureus and Klebsiella pneumoniae ranged between 4 mm and 15 mm. 22 The maximum inhibition zone (13.5 mm) in the present study was within this reported range.…”
Section: Discussionmentioning
confidence: 99%